Undergraduate nursing students' knowledge of aging, attitudes toward and perceptions of working with older adults in Kathmandu Nepal - Saruna Ghimire; Nitisha Shrestha; Karen E. Callahan; Dhirendra Nath; Binaya Kumar Baral; Nirmala Lekhak; Devendra Raj Singh (Elsevier, 2019)
Objectives: This study aims to examine Nepalese undergraduate nursing students' knowledge of aging, attitudes towards older adults and perceptions of working with older adults, and to assess differences in these outcomes by socio-demographic characteristics as well as type of nursing program. Methods: A cross-sectional study was conducted among 385 undergraduate nursing students in six nursing colleges located in the Kathmandu Valley. Knowledge of aging, attitudes toward older adults and perceptions of working with older adults were assessed using standardized tools, the Palmore Facts on Aging Quiz, Kogan's Attitudes towards Older People Scale, and Nolan's Intent to Work with Older People Questionnaire, respectively. Results: The mean knowledge scores on older adults and aging were relatively low; participants scored an average of 26.9 out of 50. Scores assessing attitudes towards and perceptions of working with older adults were more favorable. Compared to students pursuing a Bachelor of Science in Nursing (BSN), students pursuing a Bachelor of Nursing (BN) had a significantly higher score on the knowledge, attitudes and perception of aging scales. Linear regression analyses showed that the students' knowledge of aging (β = 0.55; 95% CI = 0.25-0.86) and perceptions of working with older adults (β = 0.22; 95% CI = 0.05-0.38) had a significant positive association with their attitudes toward older adults. Conclusions: Undergraduate nursing students in the Kathmandu Valley of Nepal displayed a relatively low level of knowledge, but a positive attitude towards older adults, and a positive perception of working with older adults. Observed differences in knowledge, attitude, and perception scores between students in BSN and BN programs needs further investigation; closing this gap may be important for bolstering undergraduate gerontological preparation in Nepal. Keywords: Aged, Attitudes, Knowledge, Perceptions, Students, Nursing, Nepal